1994
DOI: 10.1111/j.1365-2710.1994.tb00675.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and use of a gastropathy index for ranking the safety of non-steroidal anti-inflammatory drugs in the elderly

Abstract: This study, conducted at the Royal Devon & Exeter Hospital, Department of Geriatric Medicine, was carried out using 2987 sets of admission data. The number of patients taking non-steroidal anti-inflammatory drugs was identified together with a suite of clinical factors used to indicate the presence of gastrointestinal pathology. From this a gastropathy index was developed to establish a rank order for the individual drugs. Ketoprofen, piroxicam and fenbufen were all significantly associated with factors sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Diclofenac and ibuprofen are the most commonly prescribed anti-inflammatory drugs, both of which have a good safety record (Langman et al, 1994), whereas ketoprofen (trade name Oruvail) is not commonly prescribed, perhaps because it carries a higher risk of gastro-intestinal side-effects (Trewin et al, 1994). This is reflected in the different levels of recognition of these drugs.…”
Section: Names Of Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…Diclofenac and ibuprofen are the most commonly prescribed anti-inflammatory drugs, both of which have a good safety record (Langman et al, 1994), whereas ketoprofen (trade name Oruvail) is not commonly prescribed, perhaps because it carries a higher risk of gastro-intestinal side-effects (Trewin et al, 1994). This is reflected in the different levels of recognition of these drugs.…”
Section: Names Of Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…Celecoxib, Rofecoxib, 69 Drug with low gut toxicity, e.g. Ibuprofen, Diclofenac, 70 , 71 Drug with intermediate toxicity, e.g. Ketoprofen, Flurbiprofen, 71 Drug with very high toxicity, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…For example, comparative studies have almost invariably reported that ibuprofen is one of the safest NSAIDs. 12,16,31,32 A recent study has shed light on why this occurs, and points out one of the fallacies of doing comparative studies without knowing why a particular drug was chosen. For example, ibuprofen was most likely to be given to patients with mild disease requiring intermittent therapy, whereas patients with serious inflammatory conditions were much more likely to receive a drug with high COX-1 activity such as piroxicam.…”
Section: Causes Of Peptic Ulcermentioning
confidence: 99%